(untitled) (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
The study aimed to assess workers’ perception of autonomy, attentional control for multitasking, and well-being. The research is a quantitative, descriptive, cross-sectional survey. Administrative technicians in education at the Federal Institute of Santa Catarina responded to the instruments. There is a negative relationship between attentional control for multitasking and well-being at work, that the dimension of autonomous motivation of autonomy is related to well-being and attentional control for multitasking is related to autonomous motivation. The study contributes to advancing the understanding of behavioral, cognitive, and emotional issues in the context of telework.